Silicon as a ubiquitous contaminant in graphene derivatives with significant impact on device performance. Issue 1 (December 2018) - Jalili, Rouhollah; Esrafilzadeh, Dorna; Aboutalebi, Seyed; Sabri, Ylias; Kandjani, Ahmad; Bhargava, Suresh; Della Gaspera, Enrico; Gengenbach, Thomas; Walker, Ashley; Chao, Yunfeng; Wang, Caiyun; Alimadadi, Hossein; et al.
Abstract Silicon-based impurities are ubiquitous in natural graphite. However, their role as a contaminant in exfoliated graphene and their influence on devices have been overlooked. Herein atomic resolution microscopy is used to highlight the existence of silicon-based contamination on various solution-processed graphene. We found these impurities are extremely persistent and thus utilising high purity graphite as a precursor is the only route to produce silicon-free graphene. These impurities are found to hamper the effective utilisation of graphene in whereby surface area is of paramount importance. When non-contaminated graphene is used to fabricate supercapacitor microelectrodes, a capacitance value closest to the predicted theoretical capacitance for graphene is obtained. We also demonstrate a versatile humidity sensor made from pure graphene oxide which achieves the highest sensitivity and the lowest limit of detection ever reported. Our findings constitute a vital milestone to achieve commercially viable and high performance graphene-based devices. Silicon-based contaminants are ubiquitous in natural graphite, and they are thus expected to be present in exfoliated graphene. Here, the authors show that such impurities play a non-negligible role in graphene-based devices, and use high-purity parent graphite to boost the performance of graphene sensors and supercapacitor microelectrodes.